Smoke-flavoured cod obtained by a new method using water vapour permeable bags. (June 2016) - Rizo, Arantxa; Fuentes, Ana; Fernández-Segovia, Isabel; Barat, José M.
Abstract: The objective of this study was to adapt and optimise a new smoking-salting process developed for salmon to obtain smoke-flavoured cod. Fish was processed at 60% relative humidity (RH)/5 °C for 24 h using different salt doses. During process optimisation, new conditions were studied (salt dose, RH, processing time). Smoke-flavoured cod showed higher salt and moisture content than the salmon samples, which required a higher salt concentration to reach similar aw values. Process optimisation allowed the exudate to evaporate when the process lasted 72 and 96 h. The samples obtained with the 2% salt dose, 60% RH and 96 h gave the closest levels of moisture, salt and aw to commercial products. This new smoking-salting could substitute traditional procedures as it minimises product handling and brine wastes, reduces processing steps and can be applied to different fish types by adapting processing parameters. Highlights: We propose a new methodology to obtain smoke-flavoured cod. Water vapour permeable (WP) bags allow the complete exudate evaporation. This novel process can be implemented for fatty and lean fish. WP bags enable fish dehydration while protecting products from contamination. The new method reduces processing steps, brine wastes and fish handling.